Oro-facial characteristics and the surgical correction of patients affected by beta-thalassaemia: a review of the literature and report of a case - Tehranchi Azita; Behnia Hossein; Ghochani Mostafa Sadeghi; Younessian Farnaz (Sciendo, 2015)
Despite the fact that recent medical advances have improved the quality of life and increased the life expectancy of patients suffering from thalassaemia, no standard strategy or clinical guidelines are available for the correction of the presenting craniofacial anomalies. The aim of the present study is to review the craniofacial features of affected patients, and to discuss the orthodontic and orthognathic surgical treatment options available to manage the associated and characteristic facial deformity.